Analisis Self-Compassion pada Mahasiswa Rantau Universitas Islam Negeri Walisongo Semarang - Lestari, Sri Puji; Annisa, Ishma; Aini, Dewi Khurun (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Most students have faced academic demands, adaptation and socialization, especially those who have migrated far from home, which often makes them emotionally unstable. To overcome these emotions, you need an attitude of compassion towards yourself (self-compassion), namely accepting suffering, shortcomings and failures as part of life with full compassion for yourself. The purpose of this research is to analyze self-compassion in overseas students. This research uses an online qualitative approach. The subjects of this research were 5 overseas students from the Walisongo State Islamic University, Semarang. Data collection was carried out using semistructured interviews. The research results show that overall self-compassion among overseas students can be said to be quite good. However, each informant has their own differences in giving affection to themselves.